FR2.2: Gender-based assessment of rice and rice seed production in Nioro hub, Senegal - Ndour, Maimouna (Africa Rice Center, 2022)
In the central part of Senegal, farmers are threatened by some abiotic stress including salinity and toxicity such that farmers abandoned rice farming in some areas. The pressures to sustain the farmers' livelihood sources are intense, involving land hire in the less-affected areas. From a gender perspective, these conditions are particulary worrying because they are compromising the essence of the role of the woman in the household: rice growing for food in the lowland fields is a traditional activity of the woman, the man is involved in cash crop production in upland ecology (groundnut and millet). Hence producing rice is essentially the woman's contribution to the household's food consumption, noting that men are becoming involved in growing upland rice, with the introduction of suitable varieties. This study targeted to investigate the women and men specific seed needs, challenges, and opportunities to make rice and rice seed production more beneficial to women, by providing them stress tolerant verities for lowlands and identifying sustainable business models adoption and dissemination. We conducted focus group in three villages with separate groups of men; women and young people and quantitative data collection with a sample of 60 farmers in each village, to identify the constraints to rice farming and to assess the producer's awareness of this improved varieties. The abiotic stressors decimate the crops and then the stress tolerant varieties and production of seeds sparked a new interest in rice cultivation in this region. Additional efforts are required to implement sustainable business models for seed production.